The presence and the power the significance of the Holy Spirit in the life and ministry of Jesus - Hawthorne, Gerald F. 1925- (Waco, TX Word, 1991)
Includes bibliographical references and indexes.
Keywords: Holy Spirit -- biblical teaching; Bible. N.T. Gospels -- criticism, interpretation, etc; Jesus Christ -- person and offices